The Use of Virtual Reality Technology in Higher Education as a Method and Means of Teaching (Eurasian Research Bulletin, 2023)
In work the experimental training programs created in the present virtual reality are submitted, their influence on thinking and psychological conditions of the person is tracked. The virtual reality is considered as special the information environment in which all objects are submitted in 3-D measurements, there is a wide animation, change of images at a mode of real time and experience of effect of presence. Thus interpretation of a virtual reality as method, means and technology of training is proved.